2008
DOI: 10.1111/j.1365-2648.2008.04794.x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s stories of their experiences as overweight patients

Abstract: Awareness of these findings could reform understanding of women's experiences as overweight patients and raise the consciousness of nurses worldwide to develop sensitive communication strategies and healthcare environments that support holistic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
135
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(144 citation statements)
references
References 15 publications
7
135
0
2
Order By: Relevance
“…17 Focus groups and surveys have found that patients desire a respectful relationship with their physician and may avoid the health-care system if such a relationship does not exist. 9,12 We postulate that physician respect may play a role in patients with obesity avoiding the health-care systems and receiving less preventive care and less education about their health documented in other studies, but more studies are needed to determine specifically what additional consequences may occur as a result of lower respect. 12,14,15,20 Future research should explore the impact of physician negative attitudes associated with obesity on the health-care processes and outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Focus groups and surveys have found that patients desire a respectful relationship with their physician and may avoid the health-care system if such a relationship does not exist. 9,12 We postulate that physician respect may play a role in patients with obesity avoiding the health-care systems and receiving less preventive care and less education about their health documented in other studies, but more studies are needed to determine specifically what additional consequences may occur as a result of lower respect. 12,14,15,20 Future research should explore the impact of physician negative attitudes associated with obesity on the health-care processes and outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a study of obese females, participants indicated a desire for a respectful relationship with their physician and would avoid health-care visits if such a relationship did not exist. 9 While a general bias towards obesity has been documented in the literature, little is known about the respect a physician has for a patient with obesity and how that may impact the patient's care. In this study, we examine the relationship between physician respect and patient obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vår studie bekrefter det andre har funnet; personer med sykelig overvekt ønsker å bli møtt som hele mennesker, få anerkjennelse fra helsepersonell, tilrettelagt hjelp til vektregulering gjennom primaerhelsetjenesten og sosial støtte gjennom selvhjelpsgrupper (29). De fleste vet hva de bør gjøre, men at det er vanskelig å legge om vanene.…”
Section: Diskusjonunclassified
“…Not only there is a problem with attitudes, but sometimes, even the environment is not suitable for the needs of people with obesity (e.g., narrow armchairs, medical instrumentation that doesn't fit, scales located in places where there is no privacy), and this can discourage a call for help [10,11].…”
mentioning
confidence: 99%